Investigations of some chemical constituents in coleus amboinicus - Robles, Reynaldo F., Jr. (Animo Repository, 1986)
In this study, dried leaves of Coleus amboinicus Lour. (locally known as Oregano) was extracted with methanol using a Soxhlet apparatus. The crude extract was chromatographed using solvents of increasing polarity. Fractions collected were monitored by thin layer chromatography in different solvents. Fractions with similar TLC spots were combined resulting in 6 major fractions. These were further fractionated until seemingly pure fractions were obtained as indicated by their TLC's in various developing solvents. The presence of carvacrol and thymol in Coleus amboinicus Lour. was confirmed in this study. Previous reports indicate that the carvacrol is always accompanied by some small amount of thymol since the similarity in their structure poses difficulty in their separation. However, this work has shown that carvacrol could be obtained in a pure state rather easily by subjecting the Soxhlet extract to regular column chromatography. One of the fractions yielded a non-polar 1,4-disubstituted benzene derivative however, its structure could not be further characterized. Further study of this isolated substance is noteworthy since the isolation of any 1,4-disubstituted benzene derivative has not yet been reported for Coleus amboinicus Lour. Two other solids with melting points 165-170-'C and 150-155'C were isolated. The 1H-NMR of both solids showed the characteristic pattern of sterols. Further instrumental analyses such as 13C-NMR indicated the solids to be mixtures of sterols. The solid from fraction 5 is possibly a mixture of stigmasterol and campesterol based on their melting points and their spectra. Characterization of the substances were done using IR, 1H-NMR (60MHz and 300 MHz), and 13C-NMR.